4-Nitroaniline-2,4,6-trimethoxybenzaldehyde (1/1) - Tan, Kong Wai; Ng, S.W.; Asiri, A.M.; Khan, S.A. (International Union of Crystallography, 2010)
In the title co-crystal, C6H6N2O 2.C10H12O4, the two components are held together by an N-H⋯Oaldehyde hydrogen bond. Adjacent co-crystals are linked by weaker N-H⋯Onitro hydrogen bonds, forming a linear chain. The two aromatic rings of the components are aligned at 75.2 (1)°. The crystal studied was a non-merohedral twin with a 24% minor component.